Proceedings of the 52nd Annual Design Automation Conference 2015
DOI: 10.1145/2744769.2744882
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of PEVs for energy cost minimization and frequency regulation in the smart grid accounting for battery state-of-health degradation

Abstract: Plug-in electric vehicles (PEVs) are considered the key to reducing the fossil fuel consumption and an important part of the smart grid. The plug-in electric vehicle-to-grid (V2G) technology in the smart grid infrastructure enables energy flow from PEV batteries to the power grid so that the grid stability is enhanced and the peak power demand is shaped. PEV owners will also benefit from V2G technology as they will be able to reduce energy cost through proper PEV charging and discharging scheduling. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The reason for considering storage price is that the stored power and bought power are homogeneous commodities. Present decisions on charging or discharging will influence the future purchases of power [28], so that the storage price is a kind of potential cost. Let ∆ i denote the variation of the energy stored in the batteries during the (dis)charging procedure.…”
Section: B Large-slot Layer: Capacity Provisioning Of Dcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for considering storage price is that the stored power and bought power are homogeneous commodities. Present decisions on charging or discharging will influence the future purchases of power [28], so that the storage price is a kind of potential cost. Let ∆ i denote the variation of the energy stored in the batteries during the (dis)charging procedure.…”
Section: B Large-slot Layer: Capacity Provisioning Of Dcsmentioning
confidence: 99%
“…Line 3 is used to update the value of F PC i according to the revised q i . Every time we solve a new version of q i , we plug the corresponding F PC i into (28) and obtain a new version of problem P1, which can be solved by standard convex programming methods, such as the SQP method shown in Line 4. In Appendix A, we give mathematical proofs that our proposed SCP algorithm can always find the globally optimal solution of problem P. Besides, the SCP algorithm converges fast, as it can find the optimal solution of problem P by solving problem P1 no more than 2 × I i=1 N i times .…”
Section: A Solutions Of Problem Pmentioning
confidence: 99%
“…Firstly, we consider the energy conversion efficiency of battery charging and discharging [34], denoted as η i (δ i ) or η i for short, where η i ∈ (0, 1). The relationship between Q bat i and ∆ i is given by Q bat i = g(∆ i ), where g(∆ i ) is defined as…”
Section: Model Of Power-storage Schedulingmentioning
confidence: 99%
“…It is observed that η i may be well fitted with a power function or an exponential function, which will be further analyzed in our simulations. Secondly, another issue that we should be concerned about is that present decisions on charging or discharging will influence the future cost [34], which is denoted as potential cost. For instance, the more the power that the battery discharges at present, the more the power it will have to charge in the future, which will increase the future power cost.…”
Section: Model Of Power-storage Schedulingmentioning
confidence: 99%
“…However, few studies have actively incorporated battery aging as part of regulation operation or bidding optimization objectives. References [20], [21] take into account the battery lifespan in regulation control optimization, using an aging model that is too simple to reflect properly the complex battery cycle aging mechanisms. The results in [22] incorporate the battery aging cost into regulation bidding strategies, but the proposed method does not optimize real-time operations.…”
Section: Introductionmentioning
confidence: 99%